Microwave-assisted extraction of sulfated fucans from brown seaweed and evaluation of fungal strains for enzymesactive production toward this class of polysaccharide - Rodríguez-Jasso, Rosa María (2010)
Sulphated polysaccharides from brown seaweedss comprise a complex group of macromolecules with a wide range of important biological properties such as anticoagulant, antioxidant, antiproliferative, antitumoral, anticomplementary, anti-inflammatory, antiviral, antipeptic and antiadhesive activities. Fucoidan is one of the main sulphated fucan, mostly interesting for their biological activities specially the potential to inhibit HIV reverse transcriptase and the possible application as active compound in antiretroviral drugs. However, algae remain largely unexploited and seaweeds can be found in sufficient amount for the commercial exploitation. Usually, most of the processes to recover sulfated polysaccharides from natural sources consist in acid extractions during long reaction times. Specific enzymes able to degrade fucoidan matrix (fucoidanases) are important tools to establish structural characteristics and biological functions of this polysaccharide. Such enzymes, have been only isolated from marine organisms. Reports of fungal microorganisms with enzymatic activity over this sulfated-polysaccharide are scarce. The aims of the present work were: 1) to recovery of sulphated polysaccharides (fucoidan) by microwave-assisted extraction under different operational conditions and 2) the identification of fungal strains able to growth over fucoidan-based media and to produce active fucoidanases.